Identification and Molecular Characterization of the Switchgrass AP2/ERF Transcription Factor Superfamily, and Overexpression of PvERF001 for Improvement of Biomass Characteristics for Biofuel - Wuddineh, Wegi A.; Mazarei, Mitra; Turner, Geoffrey B.; Sykes, Robert W.; Decker, Stephen R.; Davis, Mark F.; Stewart, C. Neal (Frontiers in Bioengineering and Biotechnology, 2015)
The APETALA2/ethylene response factor (AP2/ERF) superfamily of transcription factors (TFs) play essential roles in the regulation of various growth and developmental programs including stress responses. Members of these TFs in other plant species have been implicated to play a role in the regulation of cell wall biosynthesis. Here, we identified a total of 207 AP2/ERF TF genes in the switchgrass genome and grouped into 4 gene families comprised of 25 AP2-, 121 ERF-, 55 DREB (dehydration responsive element binding)-, and 5 RAV (related to API3/VP) genes, as well as a singleton gene not fitting any of the above families. The ERF and DREB subfamilies comprised 7 and 4 distinct groups, respectively. Analysis of exon/intron structures of switchgrass AP2/ERF genes showed high diversity in the distribution of introns in AP2 genes versus a single or no intron in most genes in the ERF and RAV families. The majority of the subfamilies or groups within it were characterized by the presence of one or more specific conserved protein motifs. In silico functional analysis revealed that many genes in these families might be associated with the regulation of responses to environmental stimuli via transcriptional regulation of the response genes. Moreover, these genes had diverse endogenous expression patterns in switchgrass during seed germination, vegetative growth, flower development and seed formation. Interestingly, several members of the ERF and DREB families were found to be highly expressed in plant tissues where active lignification occurs. These results provide vital resources to select candidate genes to potentially impart tolerance to environmental stress as well as reduced recalcitrance. Overexpression of one of the ERF genes (PvERF001) in switchgrass was associated with increased biomass yield and sugar release efficiency in transgenic lines, exemplifying the potential of these TFs in the development of lignocellulosic feedstocks with improved biomass characteristics fo